From Narration to Interpretation: Mapping Hadith Functions in Tafsir al-Dur al-Manthur (Surah al-Fatihah Case) - Muhtasorul Muzanni Ahmad; Muhammad Muslich Aljabbar (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2025)
This study investigates the use of hadith in Al-Dur al-Manthur fi Tafsir bi al-Ma'thur by Imam Suyuti, a classical tafsir that applies the al-athari method by relying heavily on narrations from the Prophet Muhammad, his Companions, and the Tabi'in. The main issue addressed in this research is the absence of a detailed classification or mapping of how these hadiths are utilized within the commentary, which causes the tafsir to appear as a compilation of narrations rather than a critical analysis of the Qur'anic content. The purpose of this study is to classify the types of hadith based on their functional roles in the interpretation of verses, using Surah al-Fatihah as the primary focus.The research employs a qualitative method with data gathered through literature review. The primary data source is Al-Dur al-Manthur, while secondary sources include scholarly books and journal articles relevant to Qur'anic exegesis and hadith studies. The analytical approach is descriptive-analytical, aiming to identify patterns and categorize hadith usage. The findings reveal that hadiths in this tafsir serve seven distinct purposes: explaining alternative names of a surah, indicating the location of revelation, describing the benefits and virtues of a surah, providing explicit interpretations of verses, highlighting qira'at variations, and elaborating on legal implications. This study contributes to the field of Qur'anic interpretation by offering a structured framework for understanding how hadith is functionally employed in one of the most renowned traditional commentaries.